Living with restraint: Reactions of nurses and lived experience workers to restrictions placed on the use of prone restraint. (25th March 2022) - Meehan, Tom; McGovern, Megan; Keniry, Donnacha; Schiffmann, Ian; Stedman, Terry
Abstract: Despite recent changes to mental health policy in Australia and overseas, physical restraint continues to be widely employed in mental health services. While mental health nurses have a critical role to play in supporting initiatives designed to reduce restraint, it is unclear how they feel about moves to restrict the use of prone restraint. In this qualitative study, focus group interviews were conducted with mental health nursing staff and lived experience workers (LEWs) to gain their perspectives on the use of physical restraint in general and the restrictions being placed on prone ('face down') restraint. Five themes emerged: justifying the need for restraint, reliance on the prone position, the position is not the issue, time limits, and the psychological impact. Although mental health nurses were concerned about the risks associated with physical restraint, they provided strong justification for continued use of the prone position. LEWs raised concerns about the psychological impact of prone restraint and noted the need for a greater emphasis on de‐escalation and other restraint avoidance strategies. The findings highlight the complexities and challenges to be considered when developing initiatives to reduce reliance on the use of restraint in general, and prone in particular.